مهارات التفكير الإيجابي وعلاقته بجودة الحياة الوظيفية -دراسة ميدانية بجامعة محمد بوضياف بالمسيلة- - لبصير, فاطمة (كلية العلوم الانسانية والاجتماعية جامعة محمد بوضياف المسيلة, 2020)
هدفت الدراسة الى التعرف على طبيعة العلاقة الارتباطية بين مهارات التفكير الإيجابي وجودة الحياة الوظيفية لدى موظفي جامعة محمد بوضياف بالمسيلة، كما تم استخدام مقياس التفكير الايجابي لـ عبد الستار إبراهيم (2007) حيث يتكون من (110) عبارة تتوزع على 10 مجالات وهي (التوقعات الايجابية والتفاؤل/ الضبط الانفعالي والتحكم في العمليات العقلية العليا / حب التعلم والتفتح المعرفي الصحي/ الشعور العام بالرضا/ الشعور العام بالرضا/ التقبل الايجابي للاختلاف عن الاخرين/ السماحة والأريحية / الذكاء الوجداني / تقبل غير مشروط للذات/ تقبل المسؤولية الشخصية/ المجازفة الايجابية) وبعد التأكد من صدقه وثباته على عينة استطلاعية قدرت بـ (30) موظف وموظفة اكتفت الطالبة بأربعة أبعاد فقط لاختبار علاقتها بجودة الحياة الوظيفية وهي (التوقعات الايجابية والتفاؤل/ الضبط الانفعالي والتحكم في العمليات العقلية العليا / تقبل غير مشروط للذات / تقبل المسؤولية الشخصية)، أما الأداة الثانية فتمثلت في مقياس جودة الحياة الوظيفية من اعداد (يحي النجار وعبد الرؤوف الطلاع، 2015) وبلغ حجم العينة الأساسية (100) موظف وموظفة بجامعة محمد بوضياف، ولمعالجة بيانات الدراسة تم استخدام الأساليب الإحصائية التالية (التكرارات والنسب المئوية، معامل الارتباط بيرسون معامل ألفا كرونباخ، معامل الارتباط (Rho de Spearman Correlation)، اختباري كولموغروف سميرنوف، واختبار شابيروا، وتوصلت الدراسة إلى النتائج التالية: 1- توجد علاقة ذات دلالة إحصائية بين التوقعات الايجابية والتفاؤل وجودة الحياة الوظيفية لدى موظفي جامعة محمد بوضياف بالمسيلة. 2- توجد علاقة ذات دلالة إحصائية بين الضبط الانفعالي والتحكم في العمليات العقلية العليا وجودة الحياة الوظيفية. 3- توجد علاقة ذات دلالة إحصائية بين تقبل غير مشروط للذات وجودة الحياة الوظيفية لدى موظفي جامعة محمد بوضياف بالمسيلة. 4- توجد علاقة ذات دلالة إحصائية بين تقبل المسؤولية الشخصية وجودة الحياة الوظيفية لدى موظفي جامعة محمد بوضياف بالمسيلة. 5- توجد علاقة ذات دلالة إحصائية بين مهارات التفكير الايجابي وجودة الحياة الوظيفية لدى موظفي جامعة محمد بوضياف بالمسيلة. الكلمات المفتاحية: التفكير الايجابي، جودة الحياة الوظيفية، الموظفين. الملخص بالإنجليزية: Summary: The study aimed to identify the nature of the correlational relationship between positive thinking skills and the quality of career among the employees of the University of Muhammad Boudiaf in Masila, and the positive thinking scale of Abdul Sattar Ibrahim (2007) was used as it consists of (110) phrases distributed into 10 areas, namely (Positive expectations and optimism / emotional control and control of higher mental processes / love of learning and healthy cognitive openness / general feeling of satisfaction / positive acceptance of difference from others / tolerance and comfort / emotional intelligence / unconditional acceptance of self / acceptance of personal responsibility / positive risk) and after making sure of his sincerity And his stability on an exploratory sample estimated at (30) male and female employees. The student was satisfied with four dimensions only to test its relationship to the quality of job life, namely (Positive expectations and optimism / emotional control and control of higher mental processes / unconditional acceptance of oneself / acceptance of personal responsibility). The second tool was the quality of job quality measure prepared by (Yahya Al-Najjar and Abdul-Raouf Al-Talaa, 2015) and the size of the basic sample was (100) An employee and employee at the University of Mohamed Boudiaf, and to process the study data, the following statistical methods were used (frequencies and percentages, Pearson correlation coefficient, Cronbach alpha coefficient, the correlation coefficient (Rho de Spearman Correlation), Colmogrove Smirnov test, and Shapiro test, and the study reached the following results: 1- There is a statistically significant relationship between positive expectations, optimism and quality of life for the employees of the University of Muhammad Boudiaf in Al-Masila. 2- There is a statistically significant relationship between emotional control and control of higher mental processes and quality of job life. 3- There is a statistically significant relationship between unconditional self-acceptance and quality of career among the employees of the University of Muhammad Boudiaf in Al-Masila. 4- There is a statistically significant relationship between acceptance of personal responsibility and quality of career among the employees of the University of Muhammad Boudiaf in Al-Masila. 5- There is a statistically significant relationship between positive thinking skills and quality of life for the employees of the University of Muhammad Boudiaf in Al-Masila
Keywords: التفكير الايجابي، جودة الحياة الوظيفية، الموظفين.: positive thinking, quality of career, employees.